Viking Adventure - Roderick Hunt (Oxford, United Kingdom Oxford University Press, 1997)
A lively set of playscript adaptations of the original six Magpies storybooks at Stage 8, these are ideal for consolidation and reading practice, and can be used with groups or individuals. They teach the conventions of drama and develop skills in reading aloud and shared reading. Each play has a cast list of between four and six characters including one or more narrators. There are six lines of text per page and suggestions for sound effects. The words are close to the original story and the artwork is completely re-drawn to show similar scenes to the original storybooks.
Keywords: Play / Drama -- Play / Drama